Majmu'ah Mirza Muhammad Hadi Ruswa - Ruswa, Mirza Muhammad Hadi (Lahore Sang-e-Meel Publications, 2000)
Selections from the classical works of 19th century renowned Urdu novelist.
Urdu Fiction.
Keywords: Urdu Literature -- Urdu Fiction